Vasorelaxant and hypotensive effects of an ethanolic extract of Nymphaea pubescens and its main compound quercetin 3-methyl ether 3′-O-β-xylopyranoside - Panklai, Teerapap; Ingkaninan, Kornkanok; Chootip, Krongkarn; Temkitthawon, Prapapan; Suphrom, Nungruthai; Tournier-Nappey, Maude; Girard, Corine; Demougeot, Céline; Totoson, Perle (Frontiers in Pharmacology, 2024)
Aim Nymphaea plants were traditionally used to treat diseases associated with endothelial dysfunction. The present study investigated the effects of an ethanolic extract of Nymphaea pubescens Willd. (commonly named Water Lily, WL) and its main compound 1 (quercetin 3-methyl ether 3-O-β-xylopyranoside) on vascular function in rats. Materials and methods The vasorelaxant effects of WL extract and its main compound 1 and their underlying mechanisms actions were evaluated on isolated mesenteric arteries from Wistar rats. Blood pressure and heart rate were measured in anesthetized rats after infusion (i.v) of vehicle, WL extract, compound 1 (at 0.01, 0.025, 0.05, 0.1, 0.5, and 1 mg/kg). Nifedipine was used as a positive control. Results Both WL extract and compound 1 induced vasorelaxant effects (with EC50 of 0.08±0.01 mg/mL and 42.8±6.3 µM, respectively) that were reduced by endothelium removal. A significant decrease in these relaxations was observed with L-NAME, but not with apamin-charybdotoxin or indomethacin. In endothelium-denuded condition, WL extract-induced relaxation was enhanced by 4-aminopyridine and glibenclamide while iberiotoxin and ODQ (1H-[1,2,4]oxadiazolo[4,3-a]quinoxaline-1-one) had no effect. By contrast, compound 1-induced relaxation was not changed by any of these inhibitors. Both WL extract and compound 1 enhanced sodium nitroprusside-induced relaxation and inhibited receptor-operated Ca2+ channels. Only WL extract was able to reduce PE-induced contraction (p<0.001). As compared to vehicle, infusion of WL extract and compound 1 lowered systolic and diastolic blood pressure. Interestingly, the hypotensive effect of the compound was similar to that of nifedipine. The rebound tachycardia found at the highest dose of nifedipine was not shown with WL extract or compound 1 (p<0.05). Conclusion and discussion Our study demonstrated a vasorelaxant effect of WL extract and its main compound quercetin 3-methyl ether 3-O-β-xylopyranoside, relying on the potentiation of the NO-cGMP pathway and on calcium inhibitory effects. These vasorelaxant effects were associated with a potent hypotensive effect providing pharmacological evidence to the traditional use of this plant.